Mencari Peran Islam Politik dalam Demokrasi Indonesia - Testriono, Testriono (Studia Islamika, 2024)
This article reviews Diego Fossati’s (2022) Unity through Division: Political Islam, Representation and Democracy in Indonesia. The book attempts to answer why Indonesians have become increasingly satisfied with democracy despite their country’s democratic decline in recent years. The book answers the question by focusing on an overlooked aspect of democratic practice in Indonesia, namely political representation. This book argues that the ideological division between pluralism and Islamism has profound implications for substantive representation, partisanship, and public understanding of democracy. In summary, the division over political Islam has contributed to the meaning of political participation, the consolidation of the legitimacy of democratic institutions in the eyes of Indonesians, and the eventual maintenance of democracy in Indonesia. Overall, this book provides a nuanced account of the role political Islam plays in Indonesian politics, especially with respect to ideological representation and a discussion on a democratic decline in Indonesian politics.